(untitled) - Bugg, Tim (Oxford, 1997)
This text provides a concise introduction to the molecular basis of enzyme and coenzyme action from the perspective of organic chemistry, and also discusses the major classes of enzymatic processes.
Keywords: Enzymes,Enzymes